Bleeding Small Intestine Pyogenic Granuloma on 18F-FDG PET/CT. (November 2015) - Iravani, Amir; Law, Andrew; Millward, Michael; Warner, Michael; Sparrow, Susan
Abstract : Abstract: A 53-year-old man with metastatic melanoma, in remission, presented with an 8-week history of melena and anemia. Initial investigations including upper and lower gastrointestinal endoscopy, capsule endoscopy, and 99m Tc-labeled red blood cell scan did not reveal a source of bleeding. Given the concern over melanoma recurrence, 18 F-FDG PET/CT was performed that demonstrated a focus of intense uptake in the small bowel. Uncomplicated surgical resection of the segment of jejunum containing the lesion was performed, after which the patient reported no further gastrointestinal bleeding. Histopathological assessment of the lesion was consistent with pyogenic granuloma.